Effect of subclinical mastitis on the physicochemical quality of bovine milk. - Calderón Rangel, Alfonso; Arteaga Márquez, Margarita; Rodríguez Rodríguez, Virginia; Arrieta Bernate, Germán; Vergara Garay, Oscar (Revista Científica de la Facultad de Ciencias Veterinarias, 2014)
The bovine mastitis can be classified into clinical and subclinical, according to presence or absence of clinical signs. In both cases there is an increase of somatic cells (SC) being higher for clinical mastitis. The purpose of this study was to deter- mine the effect of subclinical mastitis on physical and chemical milk components in dual purpose systems (DP). Using a non-probabilistic sampling in six DP livestock enterprises in Monteria, Cordoba (Colombia), a cross-sectional study was implemented. By California mastitis test (CMT) were selected quarters evaluated as CMT 3 to take samples, and quarters evaluated as CMT 0, in the same cow, for control. The samples were collected aseptically and were kept refrigerated until processing. The physicochemical analysis was determined by Biolac 60 equipment. The determination of casein was done by spectrophotometry, and SC count by an optical and port- able cell counter. The evaluation of the physicochemical variables and SC count were grouped into four phases (0-2 months, 2-4 months, 4-6 months and more of 6 months of lactation). Milk with cell count less than 250,000 was defined as without subclinical mastitis and with subclinical mastitis when cell count was greater than or equal to 250,000 SC/mL. The averages for total protein for milk with high and low SC counts were 2.93 Ó 0.13 and 3.12 Ó 0.13, respectively. For fat percentage, averages were 3.36 Ó 0.29 for high count milks SC and 3.70 Ó 0.46 for milk with low count of SC. Overall, milk with high counts of SC, the chemicals components decreased significantly (P_0.05) compared to the low count of cells.